Emotional needs for smart products: a case study of older people living alone in Chengdu, China - Yun, Liu; Che Me, Rosalam; Yusoff, Irwan Syah Md (Frontiers in Psychology, 2025)
Older people living alone (OPLA) face significant challenges in maintaining emotional well-being, especially in the context of rapid urbanization and social change. Smart products are increasingly viewed as promising tools to support healthy and independent aging. This study explores the emotional needs of urban OPLA in Chengdu, China, and examines their perceptions and use of smart products as emotional support tools. Using a qualitative approach, in-depth interviews were conducted with 20 OPLA aged 60 and above. Thematic analysis revealed three key themes: (A) Emotional well-being of OPLA due to living alone, (B) Efforts to satisfy emotional needs, and (C) The use of smart products to satisfy emotional needs. While many older adults adopt self-regulatory strategies and express interest in technology, low motivation and usability barriers hinder their engagement with smart products. This study highlights the need for emotionally responsive, user-friendly, and culturally attuned smart technologies. The findings offer theoretical and practical insights into promoting smart aging through inclusive design and inform policies aimed at improving emotional well-being among older adults living alone.